Palmitoylation in cardiovascular diseases: Molecular mechanism and therapeutic potential - Rongli Wang; Yi He; Yan Wang; Jing Wang; Hu Ding (International Journal of Cardiology: Heart & Vasculature)
Cardiovascular disease is one of the leading causes of mortality worldwide, and involves complex pathophysiological mechanisms that encompass various biological processes and molecular pathways. Post-translational modifications of proteins play crucial roles in the occurrence and progression of cardiovascular diseases, among which palmitoylation is particularly important. Various proteins associated with cardiovascular diseases can be palmitoylated to enhance the hydrophobicity of their molecular subdomains. This lipidation can significantly affect some pathophysiological processes, such as metabolism, inflammation by altering protein stability, localization, and signal transduction. In this review, we narratively summarize recent advances in the palmitoylation of proteins related to cardiovascular diseases and discuss its potential as a therapeutic target.